LEGAL PROTECTION OF BASKETBALL ATHLETES IN CONTRACT WITH BASKETBALL CLUB - Shafania Afdira; Mas Anienda Tien (JOSAR (Journal of Students Academic Research), 2022)
Professionally, a basketball athlete will contribute directly either playing or competing on behalf of the basketball club that recruited him. The attachment between the basketball athlete and the basketball club is a logical consequence of a legal relationship between the two parties as stated in the employment contract and other agreements that have been agreed by both parties. Everything can run smoothly if the agreement can heed the legal terms and principles in the agreement correctly, but not infrequently there are problems that arise as a result of the agreement not implementing the legal terms and the agreement correctly, giving rise to rights disputes arising from the actions of one or both parties. parties outside the agreement or the laws that were in force previously and resulted in one of the parties feeling that their rights were not realized. The type of research used was normative. The data was collected by means of library research and interviews. The data analysis method used is qualitative data analysis. The results of this study show how the rights of basketball athletes as workers in a legal relationship with the basketball club that recruited them and what forms of legal protection there are in case of problems. it is necessary to take action that must be considered by the relevant parties and institutions in order to optimize the protection of the rights of basketball athletes.